Comparative analysis of bacterial diversity and fertility of soil with and without press mud in two sites in Panay, Philippines - Billonid, Joswa G (University of the Philippines Visayas, 2021)
Press mud is a waste product from the clarification of cane juice. Farmers commonly use press mud to improve the properties of soil. Though many farmers in the Philippines are using press mud as organic fertilizer, the literature on the screening of press mud as organic fertilizer is limited. The study compared the effects of press mud on bacterial diversity and physicochemical parameters of sugar mill soil in two sites in Panay, Philippines, using DNA fingerprint and soil analysis. The results showed tht all nutrient contents increased in both areas after press mud application, except inURC Passi Sugar Central, where no increase in phosphorus ans sulfur were observed after press mud application. The domination of alphaproteobacteria in URC Passi Sugar Central soil with press mud supported the lesser phosphorus and sulfur availability in soil compared to Capiz sugar Central that is dominated by alphaproteobacteria, gammaproteobacteria, and betaproteobacteria. Bacterial diversity did not significantly increase six months after press mud application. Results of the community pattern showed that if soil samples were compared between sites, soil without press mud had a significant difference in OTU richness and carrying capacity(p,0.05). No significant difference was observed in soil with press mud between the two sites in OYU richness, carrying capacity, Shannon, and Evenness, analyses (p>0.05). statistical analysis showed a significant difference in OYU richness and carrying capacity between soil with and without press mud in both sites (p<0.05). Generally, press mud application helps increase the available nutrients, diversity, and community patterns in soil, making it a good organic fertilizer.